A FRAMEWORK FOR MEASURING RESIDENTIAL SPACE EFFICIENCY IN TRADITIONAL AND SMART INTERIOR DESIGNS - Sharma, Ruchika; Dubey, Jigyasu; Yardi, Vishal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A desire to utilize space in compact manners in residential interiors catalyzes the development of Futuristic Compact and Smart Interior Solutions. The investigation involves a comparative efficiency in regard to traditional interior design in comparison to the newer advanced smart solutions regarding ability for optimizing residential spaces in efficiency levels by considering spatial adaptability, energy efficiency, aesthetic parameters, and user satisfaction in base analysis. A mixed-method approach used to evaluate the integration of smart technologies like IoT devices, modular furniture, and automated systems into compact living spaces used both quantitative surveys, qualitative case studies, and expert interviews. Results indicate that smart interiors, apart from the advantages on spatial efficiency, provide a sustainable and personalized living environment. However, maintenance and cost barriers still remain as challenges. This is further supported by the study on the possibilities of hybrid design approaches which integrate the aesthetic permanence of traditional interiors with technological flexibility from smart solutions and open doors for innovations in urban housing design.